1999
DOI: 10.1002/(sici)1097-4555(199912)30:12<1099::aid-jrs490>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of copper and iron oxide particles embedded in an SiO2 matrix

Abstract: The structure of heat-treated sol-gel-made SiO 2 samples containing copper or iron in various amounts was studied using Raman spectroscopy and x-ray diffraction. The treatments were in air in the temperature range 200-800 • C. Copper and iron concentrations were in the range 7-55 wt%. It was found that in the samples containing copper, the metal is mainly dissolved in the SiO 2 network when the thermal treatment is at low temperatures. For higher annealing temperatures, first a copper silicate is formed and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The SRL-131 glass is thus well representative of mould-blown ancient glass. Note that we do not see any evidence of Cu 2 O or CuO Raman signatures 13,28,29 (main peaks at ¾220 and 280-300, 345 and 632 cm 1 , respectively 13,28,29 ), except the narrow component observed at ¾625 cm 1 for Cu 0 -containing glass. We think that this component does not correspond to the copper oxide signature (see further discussion).…”
Section: Raman Signaturesmentioning
confidence: 99%
“…The SRL-131 glass is thus well representative of mould-blown ancient glass. Note that we do not see any evidence of Cu 2 O or CuO Raman signatures 13,28,29 (main peaks at ¾220 and 280-300, 345 and 632 cm 1 , respectively 13,28,29 ), except the narrow component observed at ¾625 cm 1 for Cu 0 -containing glass. We think that this component does not correspond to the copper oxide signature (see further discussion).…”
Section: Raman Signaturesmentioning
confidence: 99%
“…Hematite is the most thermodynamically stable phase under certain firing conditions: at atmospheric pressure, and with temperatures around 380°C γ-Fe 2 O 3 particles aggregate, and are transformed into α-Fe 2 O 3 . In general, no intermediate phases are observed during the thermal treatment of powders, but if micro-and nanoparticles of iron oxides are dispersed in silica matrices, as in the present case, two processes can take place: the stabilization of nanometric γ-Fe 2 O 3 particles (Sartoratto et al 2007, Pérez-Robles et al 1999, and the formation of ε-Fe 2 O 3 as an intermediate phase (Tronc et al 1998). Previous work (Sartoratto et al 2007) demonstrated that a silica matrix behaves like an anti-sintering agent: where the temperature of the maghemite particles does not exceed 900-1,000°C the matrix settles them thereby avoiding their thermal transformation into hematite.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectrum of PVG shows only characteristic bands [4], marked with an open triangle in Fig. 2: one band at 442 cm −1 , due to the rocking of the Si-O-Si groups; one band at 496 cm −1 assigned to the stretching of the Si-OH groups on the pore surface; one band at 602 cm −1 due to the breathing of planar (SiO) 3 rings; one band at 800 cm −1 due to the Si-OSi bending, and one band at 976 cm −1 that can be attributed to Si-O-B stretching, due to residual boron in the PVG structure.…”
Section: Resultsmentioning
confidence: 99%
“…Nanocomposite materials formed by oxide, semiconductor or metal nanoparticles embedded in glasses have attracted much attention due to the potential practical applications of these materials in fields as optics, catalysis and magnetism [1][2][3][4][5][6][7][8][9][10]. In the case of oxide-based nanocomposites, in particular iron or titanium oxides, the main interest lies in the excellent magnetic and catalytic properties of these materials [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%